Hassi Enterprise: an automatic iron / Muhammad Syahir Anuar [et al.] - Anuar, Muhammad Syahir; Abd Sukor, Abdul Azri; Saipolamin, Haziq Asyraf; Abu Kassim, Nur Syafika; Fauzi, Nur Fatin Syahirah; Yahya, Anis Syazwani (2016)
Hassi Enterprise is a new company that operated in Malaysia. The name of this company was the combination of all the director initial words. As for the business, we are innovating a product which is make people's life easier. This product is an automatic iron.